Arteriovenous malformations in hereditary haemorrhagic telangiectasia: looking beyond ALK1-NOTCH interactions. (8th December 2015) - Peacock, Hanna M.; Caolo, Vincenza; Jones, Elizabeth A.V.
Abstract: Hereditary haemorrhagic telangiectasia (HHT) is characterized by the development of arteriovenous malformations—enlarged shunts allowing arterial flow to bypass capillaries and enter directly into veins. HHT is caused by mutations in ALK1 or Endoglin; however, the majority of arteriovenous malformations are idiopathic and arise spontaneously. Idiopathic arteriovenous malformations differ from those due to loss of ALK1 in terms of both location and disease progression. Furthermore, while arteriovenous malformations in HHT and Alk1 knockout models have decreased NOTCH signalling, some idiopathic arteriovenous malformations have increased NOTCH signalling. The pathogenesis of these lesions also differs, with loss of ALK1 causing expansion of the shunt through proliferation, and NOTCH gain of function inducing initial shunt enlargement by cellular hypertrophy. Hence, we propose that idiopathic arteriovenous malformations are distinct from those of HHT. In this review, we explore the role of ALK1–NOTCH interactions in the development of arteriovenous malformations and examine a possible role of two signalling pathways downstream of ALK1, TMEM100 and IDs, in the development of arteriovenous malformations in HHT. A nuanced understanding of the precise molecular mechanisms underlying idiopathic and HHT-associated arteriovenous malformations will allow for development of targeted treatments for these lesions.